Chronic Actinic Dermatitis in a 48-Year-Old Female: A Case Report on Clinical Insights and Treatment Strategies - Varsha Ratan Gaikwad; Shah, Akshay H.; Jha, Ambika Nand (Bangladesh Journal of Infectious Diseases, 2025)
Chronic Actinic Dermatitis (CAD) is an immune-mediated photodermatosis primarily affecting elderly males with prolonged sun exposure, though increasing reports highlight its occurrence in younger individuals, particularly those with darker skin types. CAD is characterized by pruritic eczematous lesions, lichenified papules, and plaques on sun-exposed areas, predominantly in response to ultraviolet (UV)B radiation, with some sensitivity to UVA and visible light. Concurrent photo contact allergies contribute to its pathogenesis. Despite well-established diagnostic criteria, clinical features remain crucial for diagnosis, with significant allergenic contact sensitivity observed in many cases. We report a case of a 48-year-old female with no significant medical history presenting with a longstanding, pruritic, painful rash localized to sun-exposed areas. Examination revealed eczematous patches and lichenification on the anterior neck, upper chest, forearms, and hands, involving approximately 25% of the body surface area. Her occupation as a manual labourer with significant sun exposure was a critical factor in disease onset. Photo testing confirmed heightened sensitivity to UVA and UVB radiation, leading to a diagnosis of CAD. The patient was managed with topical tacrolimus, stringent sun protection, and systemic therapy. Significant clinical improvement and sustained remission were achieved. Diagnosis of Chronic Actinic Dermatitis (CAD) relies heavily on clinical features and patient history. This case underscores the importance of occupational factors and sun exposure in CAD development. The patient’s presentation of hyperpigmented and erythematous plaques, along with depigmented lesions on the scalp, was successfully managed with corticosteroids, antihistamines, and sun protection strategies. This case highlights the significance of early recognition and tailored therapeutic approaches to achieve effective management of CAD. Bangladesh Journal of Infectious Diseases, December 2024;11(2):217-222